The Effect of E-Money, Human Development Index (Hdi), and Internet Penetration on Economic Growth in Indonesia - Ullaya Shifa Darmawan; Meiryani Meiryani (Syntax Literate, 2023)
This study is to provide insight to the public and government in understanding whether E-money, Human Development Index (HDI), and internet penetration significantly impact or not the economic growth in Indonesia in order to prevent a decline in economic value in Indonesia. This study uses quantitative methods with secondary data obtained from the official websites of Statistics Indonesia, known in Indonesia as BPS (or Badan Pusat Statistik, the Central Bureau of Statistics), Bank Indonesia (BI), and Indonesian Internet Service Providers Association (APJII). The data obtained and analyzed using multiple linear regression test the significant value or effect. As a result of this research found that e-money, the Human Development Index (IPM), and internet penetration have a significant effect on the stability of economic growth. This shows that if e-money, HDI, and internet penetration increase, economic growth will also increase